Effects of self-concept clarity, impulsivity and cognitive coping strategies on chinese adolescents' engagement in risky behaviours. - Chow, Cai Wen. (2009)
The current study examined (a) whether the association between self-concept clarity and engagement in risky behaviours is mediated by the use of adaptive cognitive coping strategies, and (b) whether the association between impulsivity and engagement in risky behaviours is mediated by the use of maladaptive cognitive coping strategies over the course of 6 months. Results of multi-level modelling analyses indicated that the relationship between adolescents’ impulsivity and engagement in risky behaviours was significantly mediated by their use of maladaptive cognitive coping strategies. In contrast to our hypotheses, the association between adolescents’ self-concept clarity and engagement in risky behaviours was not significantly mediated by their use of adaptive cognitive coping strategies.